2011
DOI: 10.1016/j.metabol.2010.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Widespread effects of nicotinic acid on gene expression in insulin-sensitive tissues: implications for unwanted effects of nicotinic acid treatment

Abstract: Nicotinic acid (NA; or niacin) has been used as a hypolipidemic agent for more than four decades. However, the mechanisms underlying the effects of NA treatment (wanted and unwanted) are still poorly understood. In the present study, we discovered that NA infusion in rats resulted in dephosphorylation (i.e., activation) of the forkhead transcription factor FOXO1 in insulin sensitive tissues such as skeletal and cardiac muscles, liver, and adipose tissue. These NA effects were opposite to the effects of insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
1
24
0
1
Order By: Relevance
“…1), suggesting that the NA-induced increase in corticosterone was mediated by ACTH. Plasma glucose was clamped at basal levels during NA infusion by glucose infusion (12); and therefore, the increases in plasma ACTH and corticosterone occurred without changes in plasma glucose.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1), suggesting that the NA-induced increase in corticosterone was mediated by ACTH. Plasma glucose was clamped at basal levels during NA infusion by glucose infusion (12); and therefore, the increases in plasma ACTH and corticosterone occurred without changes in plasma glucose.…”
Section: Resultsmentioning
confidence: 99%
“…Animals were housed under controlled temperature (22 Ϯ 2 C) and lighting [12-h light (0600 -1800 h), 12-h dark (1800 -0600 h) cycle] with free access to water and standard rat chow. At least 4 d before the experiment, the animals were placed in individual cages with tail restraints as previously described (11,12), which was required to protect tail blood-vessel catheters during the experiments. The animals were free to move about and were allowed unrestricted access to food and water.…”
Section: Animals and Catheterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we set out to characterize changes in signaling regulation upon prolonged niacin treatment. We specifically investigated effects of niacin on adipose tissue as adipose tissue has been shown to be the most affected organ at the gene expression level after 7 h of niacin treatment ( 18 ).…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…One goal of the present study was to develop an animal model of FFA rebound during continuous NA administration. Our recent study (12) showed that the ability of NA to lower plasma FFA was maintained for up to 7 h when NA was constantly infused in rats. In the present study, we extended this infusion to 24 h and tested whether this prolonged exposure to NA would cause an FFA rebound.…”
mentioning
confidence: 98%